Effect of polyethylene glycol on in vitro gas production and digestibility of tannin containing feedstuffs from North African arid zone - (:unkn) unknown (My University, 2009)
The influence of tannins present in arid zone forages from North Africa: Aristida plumosa, Danthonia forskahlii, Astragalus gombiformis, Genista saharae, two date palm fractions (leaves and racemes), and vetch-oat hay taken as control on in vitro gas production and in vitro organic matter digestibility (IVOMD) was evaluated. Chemical analysis revealed the low nutritional quality of these forages. They were high in NDF, ADF and lignin (679.5, 455.7 and 86 g/kg DM, respectively) and low in nitrogen (< 12 g/kg DM) except for Astragalus that had 20 g N/kg DM. Phenolic compounds (total phenols, total tannins and total condensed tannins) were 61.8, 49.1 and 36.2 g/kg DM for palm leaves followed by Astragalus, racemes, Genista, Aristida and Danthonia. Gas production ranged between 55.2 and 152.6 mL/g DM whereas IVOMD ranged between 21 and 56.5%. Addition of PEG resulted in an overall increase in both gas production (20.2%) and IVOMD (30.7%), with the exception of Danthonia and Aristida. The largest increment for gas production was recorded for Aristida (low tannins content). However, the higher increase in IVOMD was noted for racemes, Astragalus and palm leaves (high tannins content). The variable responses among forages studied suggest that factors other than phenolic compounds also affect in vitro fermentation.
Keywords: African Research